Flexible Wearable Antenna on Electromagnetic Band Gap using PDMS substrate - Adel Y. I. Ashap; Z. Z. Abidin; S. H. Dahlan; H. A. Majid; S. K. Yee; Gameel Saleh; Norun Abdul Malek (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
A robust and low-profile electromagnetic band-gap (EBG) based on flexible wearable antenna covering 2.4 GHz frequency band is presented. The incorporated EBG with antenna reduces the  radiation into the human body around 17 dB and decreases the impacts of frequency detuning. The overall dimension of the antenna integrated with EBG is 56 x 56 x 4 mm3 with relative impedance bandwidth of 8.3% is achieved. The proposed design has improved the gain up to 7 dBi. Specific absorption rate (SAR) assessment is also studied to certify the performance of the antenna when it is located proximity to human tissue. The flexible antenna with aforementioned performances could be chosen as a good candidate for integration into a range of wearable devices for medical application.